Research advances on NLRP3 inflammasomes in organ transplantation - Wang, Kun; Luo, Hong; Ma, Xiao-jie; Zhang, Yu; Chen, Yu-xiang; Li, Tao; Wang, Yi; Jiang, Hong-tao (Frontiers in Immunology, 2026)
Organ transplantation is a life-saving therapy for end-organ failure; however, long-term outcomes are limited by complications such as ischemia-reperfusion injury (IRI), allograft rejection, and infection. The NLRP3 inflammasome, a key innate immune signaling platform, plays a central role in driving inflammation in these settings. Its activation follows a two-signal paradigm and contributes critically to tissue damage during IRI, bridges innate and adaptive immunity in acute and chronic rejection, and exerts context-dependent roles, either protective or detrimental, during infection. Although targeting NLRP3 through genetic, pharmacological, or cellular approaches shows therapeutic promise in preclinical studies, clinical translation remains challenging. Future efforts should focus on refining these strategies and elucidating its interplay within broader immune networks to improve transplant outcomes.